Analysis of the Effect of Cutting Variables against Surface Hardness - Ery Diniardi; Sri Anastasia Yudistirani; Hasan Basri; Anwar Ilmar Ramadhan (Faculty of Engineering Universitas Muhammadiyah Jakarta, 2021)
Indonesia is one of the developing countries and is actively pioneering development, especially development in the industrial sector. The industry that is quite developed at this time is the manufacturing industry which produces a finished product that can be directly used by consumers. These products are expected to have a high enough quality level so that they can compete in the market. To support this quality, one of the factors is to pay attention to the level of precision of the workpiece in this case is the level of surface roughness of the object or product produced. The surface roughness value is obtained from the tests carried out on the product which has an average surface value (Ra) and a maximum roughness value (Ry). To achieve the desired roughness value, it is necessary to make improvements in metal forming work. In the variable cutting with variations in cutting speed, it is said that the cutting speed on work with smaller diameter objects should use a high cutting speed. Feeding thickness that is too large can cause high surface roughness values and high rotation at low cutting speeds to produce a smooth surface but takes a long time. With the selection of the speed of ingestion that varies for the price of the ingestion speed of 43.52 m/minute, the surface roughness value is 6.78 m, the speed is 48.32 m/minute, the surface roughness value is 3.64 m and the ingestion speed is 59.25 m. /min the surface roughness value is 6.14 m. Meanwhile, for the infeed thickness which varies for a feed thickness of 1.2 mm, the surface roughness value is 4.06 m; a feed thickness of 2.4 mm obtained a surface roughness value of 27.82 um and a feed thickness of 3.2 mm obtained a surface roughness value of 7.02 m.